International trade and the Australian economy - Snape, Robert Hugh. (Australia Longmans, 1969)
This book is the first in a series aimed at providing a range of specialized and concise studies of various aspects of the Australian economy
Includes bibliographical references.
osa 24/1/19
Loans
Keywords: Balance of payments; Australia